(untitled) (Research, Society and Development, 2021)
Prenatal care is of great importance for a healthy pregnancy, preventing and early detecting possible complications inherent to pregnancy and thus reducing maternal and fetal morbidity and mortality. As one of the most prevalent complications, gestational diabetes mellitus has a great impact on maternal-fetal health and can cause short- and long-term complications. In order to verify the incidence and mortality of complications of pregnancy, childbirth and the puerperium and mortality due to diabetes mellitus during pregnancy in Brazil. Data collection was carried out in the Information Technology Department of the Unified Health System (DATASUS) from 2017 to 2019, based on the SUS Hospital Information System (SIH/SUS) and the Mortality Information System (SIM ). Therefore, it was found that maternal mortality due to diabetes mellitus in pregnancy in Brazil there was an increase of about 18.18% from 2014 to 2015 and 15.38% from 2015 to 2016. From 2016 to 2017, there was an increase percentage decrease of 40%, followed by an increase of 40% between 2017 and 2018 and a subsequent decrease between 2018 and 2019 of 26.66%. In short, gestational diabetes mellitus was not considered the main cause of deaths in the period studied, however, it is a disorder that must be treated and detected early, due to the fact that it can lead to the development of complications for both the pregnant woman and the fetus.